ELP6 and PLIN5 Mutations Were Probably Prognostic Biomarkers for Patients With Gastric Cancer - Di, Ji; Chai, Yan; Yang, Xin; Dong, Haibin; Jiang, Bo; Ji, Faxiang (Frontiers in Medicine, 2022)
Purpose: Gastric cancer (GC) is the fifth leading cancer around world. And prognosis of GC patients is still undesirable. Our study aimed to explore potential prognostic biomarkers for GC patients. Methods: The clinical samples were collected from the Qinghai University Affiliated Hospital, which were subjected to the whole exome sequencing (WES). The other GC related data was obtained from The Cancer Genome Atlas (TCGA) database. Cross analyses were done to determine the candidate genes. And the final mutated genes were determined by survival analyses, univariate and multivariate Cox regression analyses. CIBERSORT and GSEA were used for immune cell infiltration analysis and functional enrichment, respectively. Results: After cross analyses, 160 candidate mutated genes were identified. And mutated ELP6 and PLIN5 were significantly independently correlated with the overall survival (OS) of GC patients. GC patients with ELP6 and PLIN5 mutations had worse and better prognosis, respectively. Totally 5 types of immune cells were significantly differentially infiltrated in wild-type and mutated ELP6, PLIN5 GC samples. In mutated ELP6 and PLIN5 GC samples, totally 7 and 11 pathways were significantly enriched, respectively. Conclusions: The ELP6 and PLIN5 mutations were probably prognostic biomarkers for GC patients.